1964
DOI: 10.1002/pol.1964.100020313
|View full text |Cite
|
Sign up to set email alerts
|

Poly(1,3,4‐oxadiazoles): A new class of polymers by cyclodehydration of polyhydrazides

Abstract: Thirteen aliphatic and aromatic polyhydrazides have been converted as bulk polymer by a unique polymer by a unique polymer post reaction into high molecular weight poly(1,3,4‐oxadiazoles). This reaction proceeds by thermal cyclodehydration at 170–280°C. with elimination of water. The resulting poly(1,3,4‐oxadiazoles) have been characterized by microanalysis, inherent viscosity, x‐ray diffraction patterns, and by infrared and ultraviolet absorption spectra. Films could be pressed from the melt of polyoxadiazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 17 publications
2
35
0
1
Order By: Relevance
“…This precursor polyhydrazide is cyclized to the polyoxadiazole by heating to 200-300 • C under vacuum or heating in a dehydrating solvent such as sulfuric acid, polyphosphoric acid, or phosphoryl chloride. [19][20][21] A different synthetic procedure produces polyoxadiazoles in one step by the solution polymerization of a dicarboxylic acid or the corresponding nitrile, amide, or ester with hydrazine or its salt in polyphosphoric or sulfuric acid or a phosphorus pentoxide/methanesulfonic acid mixture. 16,22,23 In addition, aromatic polyether synthesis through aromatic nucleophilic displacement reaction has been used for the preparation of aryl ether-containing poly(1,3,4-oxadiazole)s or 1,3,4-oxadiazole-containing polyethers.…”
mentioning
confidence: 99%
“…This precursor polyhydrazide is cyclized to the polyoxadiazole by heating to 200-300 • C under vacuum or heating in a dehydrating solvent such as sulfuric acid, polyphosphoric acid, or phosphoryl chloride. [19][20][21] A different synthetic procedure produces polyoxadiazoles in one step by the solution polymerization of a dicarboxylic acid or the corresponding nitrile, amide, or ester with hydrazine or its salt in polyphosphoric or sulfuric acid or a phosphorus pentoxide/methanesulfonic acid mixture. 16,22,23 In addition, aromatic polyether synthesis through aromatic nucleophilic displacement reaction has been used for the preparation of aryl ether-containing poly(1,3,4-oxadiazole)s or 1,3,4-oxadiazole-containing polyethers.…”
mentioning
confidence: 99%
“…In the nonisothermal thermogravimetrical weight loss curve, three distinct phases of weight losses can be determined, see Figure 2 : (1) loss of absorbed water, (2) loss of water caused by the cyclo dehydration reaction of the hydrazide groups, (3) Thermo gravimetrical wei ht loss curve for polyhydrazide recorded at a heating rate of 2O"C/min in a nitrogen atmosphere .…”
Section: Nonisothermal Thermogravimetrymentioning
confidence: 99%
“…Nonetheless, this kind of polymers can be synthesized via the preparation of a polyhydrazide as a soluble precursor polymer, by the reaction of dihydrazides of dicarboxylic acids with dicarboxylic acids or diacid chlorides followed by cyclization to the corresponding polyoxadiazoles by heating at elevated temperatures or by heating in dehydrating solvents. [13] It has also been demonstrated that incorporation of flexible linkages like aryl ether and/or solubilizing groups such as hexafluoroisopropylidene and phthalide into the polyoxadiazole backbone leads to an enhanced solubility in organic solvents while still retained desirable mechanical and thermal properties. [14][15][16] On the other hand, oxadiazole derivatives are well-known electron-transporting materials used in organic light-emitting diodes (OLEDs).…”
mentioning
confidence: 99%